Book-Scanning Robots Digitize Delicate Texts. - Dumiak, M. (IEEE spectrum)
The Bavarian State Library, one of the largest in the German-speaking world, has already cast its lot with Google in the sometimes controversial struggles over digitizing and posting online the vast volume of literature that no longer is covered by copyright law. In the Bavarian State Library's basement, two machines called ScanRobots are whirring away at 700 pages per hour and are scheduled to digitize all of the four-century-old books in the library, the scanned books will be put online. Even though the ScanRobot doesn't have legs or wheels. This one turns the pages automatically. The robot is also able to recognize errors project.